A health and lifestyle framework: An evidence‐informed basis for contemporary physical therapist clinical practice guidelines with special reference to individuals with heart failure. (25th April 2022) - Dean, Elizabeth; Lomi, Constantina
Abstract: Background and purpose: This study proposes contemporary physical therapist clinical practice guidelines (CPGs) with special reference to heart failure (HF) be grounded in an evidence‐informed integrative health and lifestyle framework to not only better reflect the totality and weighting of the literature, but also in the interest of superior patient, clinical, and economic outcomes. Methods: As an illustration, a health and lifestyle framework is described to underpin, thereby complement, recently published physical therapist CPGs for individuals with HF. Results: The case for the framework, an alternative to a single‐disease biomedical perspective, is consistent with 21st century professional and epidemiologic indicators. Four themes that emerged from the HF CPGs and further support such a framework, emerged that is, limitations of conventionally constructed CPGs; physical therapists' scope of practice as "health" professionals; "best" practice in an era of NCDs including HF; and superior economic benefit. Discussion: A health and lifestyle framework underpinning contemporary physical therapist CPGs will enable clinicians to better appreciate the power of lifestyle change in maximizing the health of the heart, its healing and repair, and in mitigating and reversing signs and symptoms of cardiac dysfunction. Further, a focus on health and lifestyle will augment the benefits of the core, evidence‐based, key action statements related to exercise in the HF CPGs.